Rural territorial development policies and indigenous peoples in the Argentine Northwest (2020-2023): situated collaborative experiences - Macarena Del Pilar Manzanelli; María Paula Milana (Maskana)
The article analyzes two rural territorial development projects in the Argentine Northwest aimed at indigenous peoples: Territories and Areas Conserved by Indigenous Peoples and Local Communities (Tucumán) and the Socio-economic Inclusion Project in Rural Areas (Salta) (2020-2023). Using collaborative ethnographic approaches and macro, meso and micro levels of analysis, the article investigated criteria for addressing indigenous populations and the ways in which they intervene in their implementation. Both projects present ambiguities: they use languages ​​of sustainable rural territorial development, environmental conservation and commercial inclusion with indigenous recognition of tolerance, which shape local demands, while they are framed in territorial conflicts and breaches of indigenous rights. However, potentialities are observed in their implementations arising from the work, political-institutional capacities of the peoples involved and their articulations with technicians, which have allowed them to go beyond institutional objectives, to guarantee community ways of life in the territory.